La experiencia constitucional (1978-2000) / Gumersindo Trujillo, Luis López Guerra y Pedro González-Trevijano (dirs.) ; Luis Aguiar de Luque... [et al.] - Trujillo, GumersindoLópez Guerra, LuisGonzález Trevijano, Pedro José
Incluye referencias bibliográficas